A Staphylococcus aureus clpX Mutant Used as a Unique Screening Tool to Identify Cell Wall Synthesis Inhibitors that Reverse β-Lactam Resistance in MRSA - Bæk, Kristoffer T.; Jensen, Camilla; Farha, Maya A.; Nielsen, Tobias K.; Paknejadi, Ervin; Mebus, Viktor H.; Vestergaard, Martin; Brown, Eric D.; Frees, Dorte (Frontiers in Molecular Biosciences, 2021)
Staphylococcus aureus is a leading cause of bacterial infections world-wide. Staphylococcal infections are preferentially treated with β-lactam antibiotics, however, methicillin-resistant S. aureus (MRSA) strains have acquired resistance to this superior class of antibiotics. We have developed a growth-based, high-throughput screening approach that directly identifies cell wall synthesis inhibitors capable of reversing β-lactam resistance in MRSA. The screen is based on the finding that S. aureus mutants lacking the ClpX chaperone grow very poorly at 30°C unless specific steps in teichoic acid synthesis or penicillin binding protein (PBP) activity are inhibited. This property allowed us to exploit the S. aureus clpX mutant as a unique screening tool to rapidly identify biologically active compounds that target cell wall synthesis. We tested a library of ∼50,000 small chemical compounds and searched for compounds that inhibited growth of the wild type while stimulating growth of the clpX mutant. Fifty-eight compounds met these screening criteria, and preliminary tests of 10 compounds identified seven compounds that reverse β-lactam resistance of MRSA as expected for inhibitors of teichoic acid synthesis. The hit compounds are therefore promising candidates for further development as novel combination agents to restore β-lactam efficacy against MRSA.